Cultural Patterns in the Poetry of the God-loving and God-annihilated Poets in the Pre-Islamic Era - Janan Razzaq Kazar, Researcher; Amal Hassan Taher, Assistant Professor Dr. (lark, 2026)
This research examines the cultural patterns in the poetry of the theologians during the pre-Islamic era, analyzing a collection of poetic texts that encompass diverse themes. These themes reflect a variety of topics, with the pattern of violence and power emerging as a means of imposing authority within the tribe and demonstrating the group's strength and ability to exert influence. This, in turn, enhances the poet's status and elevates his power, manifested in images of fighting and revenge. The pattern of the transcendent self is also prominent, reflecting the poet's self-expression and the pride, honor, and enjoyment inherent in his individual existence. Furthermore, it glorifies the individual ego, allowing the poet's voice to rise within the tribe. This is evident in the representations of the transcendent self in the poetry of the theologians, where the poet expresses himself as an entity transcending reality through spiritual and intellectual concepts. The poet also expresses mortality through sorrow and the pain of separation, attributing the vicissitudes of life to fate. The research adopted the analytical cultural approach to uncover the implications of the intellectual and cultural patterns that the theologians included in their texts.
Keywords: cultural patterns; God-loving and God-annihilated poets; pre-Islamic era.